Ceramide Pathway Regulators Predict Clinical Prognostic Risk and Affect the Tumor Immune Microenvironment in Lung Adenocarcinoma - Zhang, Yuan; Chen, Jianbo; Zhao, Yunan; Weng, Lihong; Xu, Yiquan (Frontiers in Oncology, 2020)
Purpose: The ceramide pathway is strongly associated with the regulation of tumor proliferation, differentiation, senescence, and apoptosis. This study aimed to explore the gene signatures, prognostic value, and immune-related effects of ceramide-regulated genes in lung adenocarcinoma (LUAD). Methods: Public datasets of LUAD from The Cancer Genome Atlas and Gene Expression Omnibus were selected. Consensus clustering was adopted to classify LUAD patients，and a least absolute shrinkage and selection operator (LASSO) regression model was employed to develop a prognostic risk signature. CIBERSORT algorithm was used to estimate the association between the risk signature and the tumor immune microenvironment. Results: Most of the 22 ceramide-regulated genes were differentially expressed between LUAD and normal samples. LUAD patients were classified into two subgroups (cluster 1 and 2) and cluster 2 was associated with a poor prognosis. Furthermore, a prognostic risk signature was developed based on the three ceramide-regulated genes, CYCS, RELA and FADD. LUAD patients with low- and high-risk scores differed concerning the subtypes of tumor‑infiltrating immune cells. A moderate- to -weak correlation was observed between the risk score and tumor‑infiltrating immune cells. Conclusions: Ceramide-regulated genes could predict clinical prognostic risk and affect the tumor immune microenvironment in LUAD.